2020
DOI: 10.1051/kmae/2020023
|View full text |Cite
|
Sign up to set email alerts
|

Competitive dominance of Microcystis aeruginosa against Raphidiopsis raciborskii is strain- and temperature-dependent

Abstract: Microcystis aeruginosa and Raphidiopsis raciborskii (previously Cylindrospermopsis raciborskii) are both common bloom-forming cyanobacteria which can coexist but alternatively dominate in freshwater ecosystems. To predict their blooming dynamics, we need to understand the potential environmental factors determining their succession. In the present study, we examined the pairwise competition of the three M. aeruginosa strains (FACHB905, 469 and 915) with one R. raciborskii strain (N8) at three temperature level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…More specifically, Lei et al . 98 showed that the allelopathic effect of Microcystis aeruginosa towards Raphidiopsis raciborskii was strain-dependent. Therefore, using single-strain N. spumigena cultures in studies on allelopathy will not help understand the in-situ effects of N. spumigena population composed of coexistent strains.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, Lei et al . 98 showed that the allelopathic effect of Microcystis aeruginosa towards Raphidiopsis raciborskii was strain-dependent. Therefore, using single-strain N. spumigena cultures in studies on allelopathy will not help understand the in-situ effects of N. spumigena population composed of coexistent strains.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the model prediction of species competition outcomes is strongly affected by the growth variability of strains [78]. These findings demonstrate the intraspecific heterogeneity for R. raciborskii and M. aeruginosa [44].…”
Section: Competition Between R Raciborskii and M Aeruginosamentioning
confidence: 68%
“…Recent investigations have revealed high genetic and phenotypic diversity within the population of R. raciborskii [40][41][42]. The adaptation mechanisms of different strains were divergent and the competitive advantage of R. raciborskii against Microcystis aeruginosa was strain dependent [43][44][45][46]. These findings indicated apparent intraspecific heterogeneity in R. raciborskii.…”
Section: Introductionmentioning
confidence: 97%
“…and P. agardhii were the less dominant taxa in all treatments and, in particular, P. agardhii was negatively affected by the low temperature. Temperature, in general, is one of the most important factors influencing phytoplankton growth, nutrient uptake, spatial-temporal distribution in freshwater systems and competition is one of the major factor shaping phytoplankton structure and succession in freshwaters (Lei et al, 2020). In this experiment, temperature was the most significant factor affecting the growth and structure of the phytoplankton assemblage.…”
Section: R Raciborskii Competition Dynamic and Transcriptomic Experim...mentioning
confidence: 81%